Cardio-Respiratory Fitness and Autonomic Function in Patients with Major Depressive Disorder - Herbsleb, Marco; Schumann, Andy; Lehmann, Luisa; Gabriel, Holger H.W.; Bär, Karl-Jürgen (Frontiers in Psychiatry, 2020)
Patients with major depressive disorder (MDD) have an augmented risk of cardiovascular morbidity and mortality. Although a link between depression and autonomic dysfunction as well as reduced cardio-respiratory fitness (CRF) is well documented, the underlying cause is a matter of debate. Therefore, we studied the interplay between autonomic function, body composition and severity of the disease to disentangle possible physiological factors influencing the assumed lack of CRF in MDD patients. We investigated seventeen patients suffering from MDD and seventeen control subjects matched with respect to age, sex, body-mass-index, and smoking habits. A resting baseline assessment and a cardiopulmonary exercise test including a prolonged recovery period were performed to study autonomic function (i.e., heart rate responses and heart rate variability) during rest, exercise and recovery as well as CRF. Most investigated autonomic indices were significantly different at rest, during exercise as well as during recovery indicating altered autonomic modulation. Nevertheless, none of our participants was classified as chronotropically incompetent. As expected, a reduced CRF (i.e., peak oxygen uptake and peak power output, p < 0.01) was observed in patients compared to controls. In addition, a correlation of baseline heart rate and of heart rate during recovery with the ventilatory threshold 1 (p < 0.05) was found in patients only, indicating a relation to the lack of CRF. Furthermore, we observed a positive correlation of the severity of the disease with the weekly sitting time (p < 0.01) as well as a negative correlation with the activity time in the intensity domain walking (p < 0.001) and with the total score of the International Physical Activity Questionnaire (p < 0.01) for patients. This study shows that patients with MDD have altered autonomic function not only during resting conditions but also during exercise as well as recovery from exercise. Intervention studies are needed to evaluate how the described autonomic alterations can be influenced by increasing CRF due to appropriate exercise training programs.